2011
DOI: 10.1111/j.1365-2419.2011.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration and behavior of juvenile North Pacific albacore (Thunnus alalunga)

Abstract: Archival tags were used to study the seasonal movements, migration patterns and vertical distribution of juvenile North Pacific albacore (Thunnus alalunga). Between 2001 and 2006, archival tags were deployed in North Pacific albacore in two regions of the Northeast Pacific: (i) off Northern Baja California, Mexico and Southern California, and (ii) off Washington and Oregon. Twenty archival tagged fish were recovered with times at liberty ranging from 63 to 697 days. Tagged albacore exhibited five distinct, sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 27 publications
3
74
1
1
Order By: Relevance
“…Bluefin and albacore tunas tagged with ATs off northern BC (Boustany et al, 2010;Childers et al, 2011) were observed to remain off northern BC during the summer months, move southward and remain off southern BC during the winter months, and return to the area off northern BC and southern California during the following summer, similar to the horizontal movement patterns of yellowfin tagged and released off northern BC in this study. However, albacore and bluefin tunas, unlike yellowfin, are highly migratory species which eventually leave the waters off BC, and migrate back to their spawning grounds in the central and/or western Pacific (Schaefer, 2001).…”
Section: Horizontal Movements and Habitatsupporting
confidence: 69%
See 1 more Smart Citation
“…Bluefin and albacore tunas tagged with ATs off northern BC (Boustany et al, 2010;Childers et al, 2011) were observed to remain off northern BC during the summer months, move southward and remain off southern BC during the winter months, and return to the area off northern BC and southern California during the following summer, similar to the horizontal movement patterns of yellowfin tagged and released off northern BC in this study. However, albacore and bluefin tunas, unlike yellowfin, are highly migratory species which eventually leave the waters off BC, and migrate back to their spawning grounds in the central and/or western Pacific (Schaefer, 2001).…”
Section: Horizontal Movements and Habitatsupporting
confidence: 69%
“…6A) (Fiedler et al, 1998). Albacore tuna tagged and released with ATs exhibited different types of vertical behavior off BC during the day, which included repetitive bounce diving behavior to depths exceeding 200 m (Childers et al, 2011), similar to that of yellowfin in this study.…”
Section: Vertical Movements and Behaviormentioning
confidence: 66%
“…Our results do not represent a comprehensive comparison of behavior and diet of PBFT, YFT, and ALB throughout their entire ranges or ontogeny. Larger PBFT migrate to both cold temperate foraging grounds and subtropical spawning grounds (11); large YFT in the CCLME remain largely residential to EPO waters (14), and large albacore migrate to subtropical waters in the Pacific Ocean (31). The relative benefits of cardiac performance, concordant water column utilization, and foraging capacity have not been comparatively assessed in these adult tunas and are outside the scope of this study.…”
Section: Significancementioning
confidence: 99%
“…Three species remain in tropical waters throughout their life cycle, skipjack (Katsuwonus pelamis), bigeye (Thunnus obesus), and yellowfin (T. albacares); while a fourth migrates between temperate and subtropical waters, albacore (T. alalunga) (Childers et al, 2011;Collette and Nauen, 1983;Kimura et al, 1997). These species support highly productive commercial fisheries in Exclusive Economic Zones (EEZs) and international waters across the Western and Central Pacific Ocean (WCPO).…”
Section: Tuna Resources In the Tropicsmentioning
confidence: 98%